Improving the efficiency of the international payment operation by means of documentary credit at joint stock commercial Bank for Foreign trade of Viet Nam,Graduation Thesis - Le Tran Thai Phuong,Do Thu Hang
Improving the efficiency of the international payment operation by means of documentary credit at joint stock commercial Bank for Foreign trade of Viet Nam : Graduation Thesis / Le Tran Thai Phuong; Do Thu Hang supervisor .- H. : Banking Academy , 2019 .- 60 p. ; 29 cm